2021
DOI: 10.3390/jcm10040592
|View full text |Cite
|
Sign up to set email alerts
|

Trough Concentrations of Specific Antibodies in Primary Immunodeficiency Patients Receiving Intravenous Immunoglobulin Replacement Therapy

Abstract: Immunoglobulin replacement therapy is a mainstay therapy for patients with primary immunodeficiency (PID). The content of these preparations was studied extensively. Nevertheless, data regarding the effective specific antibodies content (especially in the nadir period), and, in different groups of PID patients is limited. We studied trough IgG concentrations as well as anti-Pneumococcus, anti-Haemophilus influenzae b, anti-Tetanus, and anti-Measles antibody concentrations in 17 PID patients receiving intraveno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Severe viral infections with enteroviruses, a complication seen in XLA patient, has not significantly declined in the era of IVIG therapy ( 12 ). Additionally, studies looking at trough levels of various pathogens demonstrated non-protective anti measles antibodies ( 13 ). This highlights the limited value of IVIG in protection from severe viral infections.…”
Section: Introductionmentioning
confidence: 99%
“…Severe viral infections with enteroviruses, a complication seen in XLA patient, has not significantly declined in the era of IVIG therapy ( 12 ). Additionally, studies looking at trough levels of various pathogens demonstrated non-protective anti measles antibodies ( 13 ). This highlights the limited value of IVIG in protection from severe viral infections.…”
Section: Introductionmentioning
confidence: 99%